2011
DOI: 10.1260/1351-010x.18.1-2.189
|View full text |Cite
|
Sign up to set email alerts
|

Equal Reverberance Contours for Synthetic Room Impulse Responses Listened to Directly: Evaluation of Reverberance in Terms of Loudness Decay Parameters

Abstract: This paper examines effects of listening level and reverberation time on the perceived decay rate of synthetic room impulse responses (RIRs). A listening test was conducted with synthetic RIRs having a range of listening levels and reverberation times: in the test, subjects adjusted a physical decay rate of the RIRs to match the perceived decay rate of reference stimuli. In this way, we constructed equal reverberance contours as a function of sound pressure level and reverberation time. The experiment results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…All previous experiments the authors are aware of are based on judging or comparing RTs for the same type of sound source, and sound sources were only varied from experiment to experiment (Seraphim, 1958;Lee et al, 2011;Billon and Embrechts, 2012;Tsolias and Davies, 2014).…”
mentioning
confidence: 99%
“…All previous experiments the authors are aware of are based on judging or comparing RTs for the same type of sound source, and sound sources were only varied from experiment to experiment (Seraphim, 1958;Lee et al, 2011;Billon and Embrechts, 2012;Tsolias and Davies, 2014).…”
mentioning
confidence: 99%
“…Lee et al [4] reported that both reverberation time and loudness contributed to the perception of reverberation, and the 5 dB difference was significant. They evaluated steadystate noise and its decay process as the test signal, using the A-weighted equivalent sound pressure level of the steadystate portion as loudness.…”
Section: Loudness Of Musicmentioning
confidence: 99%
“…There are generally two perspectives in previous psychological research on reverberation time. One is to seek independent physical indicators corresponding to the subjective perception of reverberation [1]- [4]. The other is to clarify the appropriate reverberation time for the size of the hall or the type of music it could host [5]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…Time-depending loudness includes as well spectral masking as the temporal effects of cochlear sound processing. Densil Cabrera and Doheon Lee 12 investigated the impression of reverberance based on loudness decay curves. The loudness decay rates are much better correlated with subjective reverberance than simple level decays.…”
Section: Room Acoustics and Psychoacousticsmentioning
confidence: 99%